The impact of the organizational climate on the job performance of working individuals - Al-Aklaby, Ayed Masoud; Al-Zari, Muhammad Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
The outcome of organizational climate among individuals within organizations is the nature of the work they do and that has an impact on their behavior. This study aimed to identify the trends personnel Directorate of Prisons towards the predominant directing climate and the level of functionality from their point of view. To achieve its goals this study used a descriptive analytical approach, where a questionnaire has been designed and distributed to a sample (40), and processed statistically using statistical analysis (SPSS) program. After analysis, many results has been reached including: The existence of negative trends at low sample about the axis (organizational structure) as one of the organizational climate axes. And a low of negative attitudes among respondents towards the axis (leadership style) as one of the organizational climate axes. The existence of negative trends at low sample about the axis (systems and procedures) as one of the organizational climate axes. The study made several recommendations including: Paying attention to officials of the General Directorate of Prisons different levels Occupation organizational climate where elements that have a large impact positively or negatively on the humanitarian and economic activities within the prison sector and activities. The need to stand on the factors that will work to create negative attitudes toward the prevailing regulatory climate with personnel Directorate patio area and processed prisons and overcome. The workers in the prison sector urged at various levels and ranks in all departments and units and departments in this sector to contribute to and participate in the industry and make decisions and try to take advantage of the positive opinions and suggestions, which they get them]].
Keywords: organizational climate; job performance; working individuals; Al-Baha prisons